IMMUNOHISTOCHEMICAL ASSAY USED TO CORRELATE LYMPHOCYTES CD3, CD8 IN PATIENTS WITH GASTRIC ADENOCARCINOMA (Academicia Globe: Inderscience Research, 2022)
This study's objectives were to define the relationship between lymphocytes CD3 and CD8 in patients with gastric adenocarcinoma and to identify these two markers in connection to some patient characteristics (patient age, gender, grade, and stage). By using an immunohistochemical assay, the expression of the relationship between CD3, CD8, and gastric cancer was evaluated. According to the findings, stomach tissue samples were taken from 60 patients who had gastrectomy and had gastric cancer. The collection of these samples took place between June 2021 and February 2022. Sixty patients included 40 men and 20 women, there ages ranged between (27-74)years, with mean age 56 years. Out of 60 patients, 34 (56.66%) had immunohistochemistry evidence of the lymphocytes marker CD3. Thus, out of 60 samples, the CD8 was found in 26 (43.3%). and the middle and lower thirds of the stomach were the only locations for the double malignancies in stages 0, I, and II, with the histological grade including 35, 21, and 4 (poor, well, and moderate) differentiation, respectively. Additionally, results showed that there was a considerably stronger correlation between CD3 positivity and each of age, gender, histological grade, and tumor stage. While there was no significant relationship between CD8 expression and the patients' ages, the positive results in cytotoxic T-lymphocyte CD8 were considerably greater associated to each of grade, gender, and histological stage of the tumor.